Analisis Kemampuan Penalaran Matematis Siswa Dalam Menyelesaikan Soal Cerita Pada Materi Pecahan Siswa Kelas III SD - Sunaisah Sunaisah; Iffatul Ulya Rosyadi; Farida Maulida; Diana Ermawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to analyze students’ mathematical reasoning abilities in solving word problems on fractions in class III SD 1 Selojari. This research uses a qualitative method with a descriptive approach. The research subjects consisted of third grade students who were selected using purposive sampling. The results of the research show that students’ mathematical reasoning abilities in solving word problems on fractions are at varying levels. Most students show difficulty in understanding the concept of fractions, especially in connecting fractions with visual and contextual representations. Some students are able to solve word problems well, but many still face difficulties in identifying relevant information and integrating it into the problem solving process. Factors that influence students’ mathematical reasoning abilities include a less in-depth understanding of the basic concepts of fractions, limited word problem practice given in class, and low student motivation to learn. Apart from that, teaching methods that are less varied and the lack of use of teaching aids or learning media also contribute to students’ low mathematical reasoning abilities.